2015
DOI: 10.1177/0894845315602120
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Among the Six Vocational Identity Statuses and Five Dimensions of Planned Happenstance Career Skills

Abstract: The current study investigated how the five components of planned happenstance skills are related to vocational identity statuses. For determination of relationships, cluster and discriminant analyses were conducted sequentially on a sample of 515 university students in South Korea. Cluster analysis revealed vocational identity statuses to be divided into six meaningful groups, as the six-cluster model originally proposed by Porfeli, Lee, Vondracek, and Weigold: achieved, searching moratorium, moratorium, fore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 32 publications
6
35
0
2
Order By: Relevance
“…One difference is that optimism had the highest correlations with the other PHCI subscales in the present study, whereas persistence had the highest correlations with the other PHCI subscales in the Korean sample in Kim, Jung, et al's study. The validity was also supported by the correlations between vocational identity status and the PHCI, which is consistent with the findings from Rhee et al ().…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…One difference is that optimism had the highest correlations with the other PHCI subscales in the present study, whereas persistence had the highest correlations with the other PHCI subscales in the Korean sample in Kim, Jung, et al's study. The validity was also supported by the correlations between vocational identity status and the PHCI, which is consistent with the findings from Rhee et al ().…”
Section: Discussionsupporting
confidence: 90%
“…Vocational identity status is a concept that classifies the career development process of individuals across three dimensions: exploration, commitment, and reconsideration (Porfeli, Lee, Vondracek, & Weigold, ). Rhee, Lee, Kim, Ha, and Lee () reported that the exploration and commitment dimensions of vocational identity status were related to higher levels of persistence and optimism, whereas the reconsideration dimension was positively related to flexibility. We expected that the current study would produce similar results as in these previous studies.…”
Section: Purpose Of the Studymentioning
confidence: 99%
“…The three processes are exploration, commitment, and reconsideration, which often yield six identity statuses: achievement, moratorium, foreclosure, diffusion, undifferentiated, and searching moratorium. Continuing studies replicate the three processes and six statuses, and empirical findings of correlates seem to support that the three processes of vocational identity development have its own uniqueness (Negru-Subtirica, Pop, & Crocetti, 2015;Porfeli, Lee, Vondracek, & Weigold, 2011;Rhee, Lee, Kim, Ha, & Lee, 2016;Sestito et al, 2015). Research using the three-dimensional model of vocational identity development is only in its initial stage, and more studies are required to understand the developmental trajectories of the processes and possible antecedents and consequences of vocational identity development.…”
Section: Vocational Identity Development During the Transition To Adumentioning
confidence: 85%
“…The planned happenstance theory [1] or otherwise the happenstance learning theory [3,18], unlike other career counselling theories eliminating the existence of unplanned events in a person's career path, treats such events as a learning experience which may turn into useful career opportunities. In accordance with this theory, chance events are inevitable and even desired [19]. The key idea behind the happenstance learning theory is that one should adopt an active position in identifying and generating, by himself/herself, planned happenstance events which may be utilised as career opportunities.…”
Section: Planned Happenstance Conceptmentioning
confidence: 99%
“…The planned happenstance theory suggests the guidelines for taking constructive action in order to create beneficial opportunities in career development [12][13][14][15][16][17][18][19][20]. To begin with, the theory places an emphasis on exploratory activities [21].…”
Section: Planned Happenstance Conceptmentioning
confidence: 99%